Prejudice and Violence in the American Workplace, 1988-1991: Survey of an Eastern Corporation - Ehrlich, Howard J. ([Verlag nicht ermittelbar], 1994)
This study was conducted to examine the nature and extent of prejudice-based mistreatment of employees in the workplace. The researchers investigated the effects of mistreatment on employees' psychological well-being, interpersonal relationships, and perceptions of the work environment. Personal interviews were conducted with 327 first-line workers at an American corporation in the middle Atlantic states to determine workers' experiences of violence, discrimination, and prejudice and their responses to such victimization. Three dimensions of victimization were explored: personal victimization, prejudiced victimization, and co-victimization. Self-reported symptoms of post-traumatic stress were identified. Data were also collected to ascertain job satisfaction and job autonomy and to determine if these factors mitigate the effects of mistreatment. Demographic information includes age, race, sex, income, education, marital status, ethnicity, religion, handicap, and sexual orientation. The company involved in the research has been kept anonymous.